Lean Manufacturing Principles in the Design and Production of Social Robots - Charles Onyeka Nwamekwe; Emeka Celestine Nwabunwanne; Fredrick Nnaemeka Okeagu; Chukwuma Godfrey Ono (International Journal of Industrial Engineering, Technology & Operations Management, 2025)
The integration of Lean Manufacturing principles in the design and production of social robots represents a pivotal advancement in the robotics industry, addressing the dual challenges of efficiency and sustainability. This paper explores the application of core Lean concepts, including waste reduction, continuous improvement (Kaizen), and process optimization, to streamline production workflows and enhance the scalability of social robots. A comprehensive review of methodologies such as Value Stream Mapping (VSM), Kanban, and Total Quality Management (TQM) illustrates their potential to minimize waste, improve quality, and optimize resource utilization. Case studies highlight successful implementations, showcasing tangible benefits such as reduced assembly times, lower inventory costs, and fewer defects. Furthermore, the paper delves into the unique challenges of producing social robots, including high customization requirements, precision demands, and cost constraints, and offers tailored Lean solutions to overcome these hurdles. Applications of Lean principles in service industries, including healthcare, education, and hospitality, are discussed, emphasizing their role in fostering innovation, enhancing customer satisfaction, and contributing to sustainability. The research also addresses limitations, including resistance to change and scalability issues, proposing future directions that leverage digital transformation and hybrid methodologies to advance Lean frameworks for the robotics sector. By synthesizing insights from academic literature and industry practices, this paper underscores the transformative potential of Lean Manufacturing in the design and production of social robots, offering a roadmap for achieving operational excellence and sustainability in this rapidly evolving field.